NEWNESS AND BOLDNESS OF APPROACHES : FOR EFFECTIVE EVANGELISATION AND MISSIOLOGY - M. Fung, Jojo (Asian Horizons, 2011)
The call for new and bold approaches to evangelization and missiology has been a perennial challenge and concern of the Asian bishops and theologians, more so for the local Churches inserted in the web of everyday relationship amongst the marginalized and believers of the different cultures and religions. Whatever the new approaches, the Church must be manifesting the sacred power of God’s Spirit in the perennial mission of proclaiming the sustainability of life with dignity and justice in the human and earth communities that is free from corrupt and violent practices because all beings, all lives and all persons are created sacred in the sight of God.